TOURISM AREA LIFE CYCLE IN LAKE TOBA - Victor Lumbanraja (Faculty of Geography, Universitas Gadjah Mada, 2012)
This research aimed to analyze both development level and pattern in tourism area aroundLake Toba basing on its life cycle (Butler, 1980). Samples were tourism spots in 7 regenciesin the area of Lake Toba; respondents included 195 householders and 198 tourists.Combined approach (qualitative and quantitative) in this research resulted in thedifferentiation within each spot in the area whose developments do not fully follow the linearline as it is assumed by Butler (1980) i.e. emphasizing the factor of tourist number as a mainindicator in a development. Empirically, all of these tourism spots, as illustrated in previousstudies, experienced a “jump” of development especially on their tourist numbers. Beside thedetermination of quantitative indicator of tourist number, this also happened due to directcorrelation with the factor of product as well as tourism attraction including demographicand economic characteristic of the market of tourists and also the factor of superstructureesp. tourism institutions and policies.